Studying the role of urban transportation sustainability in two dimensions of social sustainability and environmental sustainability in reducing urban problems - khadijeh khatiri (اکولوژی انسانی, 2024)
The rapid development of urbanization has led to an increase in demand for infrastructure such as drinking water supply, electricity grid and the creation of transportation facilities, etc. The inadequacy of the existing system or parallel management in the urban traffic management sector has increased the gap between demand and supply of transportation facilities. The consequences of an unsustainable transportation system in urban areas are bordering on threatening human health. As a result, the need to pay attention to urban planning and management was raised. The purpose of this article is to examine the role and importance of developing sustainable urban transportation in order to reduce urban problems and consequently improve the quality of urban life. The type of research is applied and the research method is descriptive and analytical, and interview and questionnaire tools have been used in line with the research objectives. It has also been collected and analyzed through statistical data and documents available in relevant departments and organizations. The results of statistical analysis showed that there is a close relationship between urban transportation sustainability and the environmental dimension. There is also a significant relationship between urban transportation sustainability and the social dimension. Finally, it is concluded that by planning based on understanding the urban space, it is possible to create the basis for the proper development of cities and the comfort of citizens.